Análisis bioeléctrico de muestras de hisopado durante y después de la infección con rinofaringitis viral mediante un Módulo de Impedancia Variable - Lexequias , Christian (2025)
This research shows the bioelectrical characterization and impedance reading of nasopharyngeal samples taken during the infection stage of a patient with viral rhinopharyngitis compared to the healthy stage of the same patient. 11 nasopharyngeal samples were taken during the initial phase of infection and 10 nasopharyngeal samples 14 days after not presenting any symptoms. The analysis was carried out in a frequency range of 10 kHz - 1 MHz using the MIVA (Module of Variable Impedance for Analysis) bioelectrical impedance equipment. The results obtained indicated a significant difference in the impedance of the samples during the different stages, which allowed establishing a range in the axes (Z' and Z'') of the Nyquist diagram when a nasopharyngeal sample comes from a case of viral rhinopharyngitis and when the sample comes from a healthy patient. In addition, it will be modified to schematize a circuit equivalent to the bioelectric behavior of the sample with the respective value of its components, which will greatly help for future research that wishes to work in the same field of study. This work is part of the vision of the INFISA Research Group to develop a less invasive method for the diagnosis of diseases that affect the respiratory and circulatory systems.